Negative electrode active material and lithium secondary battery comprising the same
By doping Zr into the lithium titanium oxide negative electrode material and coating aluminum and sulfur-containing compounds to form a lithium titanium composite, the problem of increased resistance of lithium titanium oxide during rapid charging and discharge is solved, and a lithium secondary battery with high output performance and structural stability is achieved.
Patent Information
- Application Number
- CN202080016007.6
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Priority Date
- 2019-02-22
- Filing Date
- 2020-02-24
- Publication Date
- 2025-03-07
- Estimated Expiration
- 2040-02-24
Smart Images

Figure CN113826244B_ABST
Abstract
Description
Technical Field
[0001] The present disclosure relates to a negative electrode active material and a lithium secondary battery including the same, and more particularly, to a negative electrode active material having minimized resistance increase during charge and discharge and a lithium secondary battery including the same.
[0002] This application claims priority to Korean Patent Application No. 10-2019-0021445 filed in Korea on February 22, 2019, the disclosure of which is incorporated herein by reference. Background Art
[0003] With the increasing energy costs due to the depletion of fossil energy and the growing concern about environmental pollution, the need for eco-friendly alternative energy is a basic prerequisite for future living.
[0004] Much effort has been invested in the research and development of electrochemical devices as the application fields have expanded to energy sources for mobile phones, camcorders, portable computers, and even electric vehicles.
[0005] In this regard, electrochemical devices have received more attention, and in particular, the development of rechargeable secondary batteries has been the focus of attention, and recently in the development of batteries, new electrode and battery designs for improving capacity density and specific energy have been studied and developed.
[0006] In particular, in recent years, lithium secondary batteries are used as power sources for electric vehicles (EV), hybrid electric vehicles (HEV), and micro-hybrid electric vehicles (u-HEV), and their application range is expanded to auxiliary power sources through a grid.
[0007] Micro hybrid electric vehicles partially use secondary batteries, and development of 12V dual or 48V secondary batteries for micro hybrid electric vehicles is toward higher output performance.
[0008] On the other hand, lithium titanium oxide provides an efficiency close to 100% in the first charge and discharge cycle, and due to its high driving voltage, does not form a film on the negative electrode surface by electrolyte decomposition reaction, so the application of lithium titanium oxide as a high-output negative electrode material is expected.
[0009] Therefore, in order to achieve fast charging and discharging characteristics above 20C, the use of lithium titanium oxide is necessary, but the existing lithium titanium oxide cannot meet the corresponding output requirements.
[0010] Therefore, there is still a need to develop lithium titanium oxide negative electrode materials for use in hybrid electric vehicle applications requiring high output characteristics. Summary of the invention
[0011] Technical issues
[0012] Therefore, the present disclosure aims to provide a negative electrode active material without kinetic effect, which can be used in 12V or 48V system applications.
[0013] The present disclosure also aims to provide a lithium secondary battery comprising the negative electrode active material.
[0014] Technical Solution
[0015] In order to solve the above problems, according to one aspect of the present disclosure, a negative electrode active material of the following embodiments is provided.
[0016] According to a first embodiment, there is provided a negative electrode active material for a secondary battery, comprising:
[0017] A lithium-titanium composite, comprising:
[0018] Lithium titanium oxide represented by the following Chemical Formula 1;
[0019] Zr doped into the lithium titanium oxide; and
[0020] a compound containing aluminum and sulfur coated on the surface of the lithium titanium oxide,
[0021] Wherein, based on 1M lithium titanium oxide, the aluminum and sulfur-containing compound is present in an amount of 0.4mM to 0.9mM:
[0022] [Chemical formula 1]
[0023] Li x Ti y O z
[0024] Where x, y and z satisfy 0.1≤x≤4, 1≤y≤5 and 2≤z≤12.
[0025] According to a second embodiment, in the first embodiment, the compound containing aluminum and sulfur may include Al2(SO4)3, Al2S3 or a combination thereof.
[0026] According to a third embodiment, in the first or second embodiment, the amount of the doped Zr may be 500 to 2000 ppm based on the weight of the lithium titanium oxide.
[0027] According to a fourth embodiment, in any one of the first to third embodiments, the lithium-titanium based composite may be primary particles, secondary particles formed by agglomeration of the primary particles, or a mixture of the primary particles and the secondary particles.
[0028] According to a fifth embodiment, in the fourth embodiment, an average particle diameter (D50) of the primary particles may be equal to or less than 1 μm.
[0029] According to a sixth embodiment, in the fourth or fifth embodiment, the average particle diameter (D50) of the secondary particles may be 0.5 to 20 μm.
[0030] According to a seventh embodiment, in any one of the first to sixth embodiments, the aluminum and sulfur-containing compound may be present in an amount of 0.5 mM to 0.8 mM based on 1 M lithium titanium oxide.
[0031] According to an eighth embodiment, in any one of the first to seventh embodiments, the lithium titanium oxide may be further doped with Al, S (sulfur), or both.
[0032] According to one aspect of the present disclosure, a method of manufacturing a negative electrode active material of the following embodiment is provided.
[0033] According to a ninth embodiment, there is provided a method for manufacturing a negative electrode active material for a secondary battery, the method comprising:
[0034] (a) mixing a lithium precursor, a titanium precursor and a Zr precursor to prepare a precursor mixture;
[0035] (b) heat-treating the precursor mixture at 700 to 1,100° C. to obtain lithium titanium oxide; and
[0036] (c) mixing the lithium titanium oxide obtained after the heat treatment with a compound containing aluminum and sulfur, and heat-treating the mixture at 400 to 500° C.,
[0037] Wherein, the aluminum and sulfur containing compound is present in an amount of 0.4 mM to 0.9 mM based on 1 M lithium titanium oxide.
[0038] According to a tenth embodiment, in the ninth embodiment, the lithium precursor may include Li2CO3, LiOH, LiF, Li2SO4, LiNO3, LiCl, or a combination thereof.
[0039] According to an eleventh embodiment, in the ninth or tenth embodiment, the titanium precursor may include TiO2, TiCl4, TiOCl2, TiOSO4, TiO(OH)2, or a combination thereof.
[0040] According to a twelfth embodiment, in any one of the ninth to eleventh embodiments, the Zr precursor may include Zr(OH) 4 , ZrO 2 , or a combination thereof.
[0041] According to a thirteenth embodiment, in any one of the ninth to twelfth embodiments, the compound containing aluminum and sulfur may include Al2(SO4)3, Al2S3, or a combination thereof.
[0042] According to a fourteenth embodiment, in any one of the ninth to thirteenth embodiments, the temperature of the heat treatment performed after mixing the lithium titanium oxide with the aluminum and sulfur containing compound may be 400 to 480° C., and the aluminum and sulfur containing compound may be present in an amount of 0.5 to 0.8 mM based on 1 M of the lithium titanium oxide.
[0043] According to a fifteenth embodiment, in any one of the ninth to fourteenth embodiments, the heat treatment temperature may be 450° C., and the compound containing aluminum and sulfur may be present in an amount of 0.7 mM based on 1 M lithium titanium oxide.
[0044] According to one aspect of the present disclosure, a lithium secondary battery of the following embodiment is provided.
[0045] According to a sixteenth embodiment, there is provided a lithium secondary battery, comprising:
[0046] a positive electrode comprising a positive electrode active material, a negative electrode comprising a negative electrode active material, a separator interposed between the positive electrode and the negative electrode, and an electrolyte,
[0047] Wherein, the negative electrode active material is defined in any one of the first to eighth embodiments.
[0048] Beneficial Effects
[0049] The negative electrode active material according to an embodiment of the present disclosure includes a lithium-titanium based composite, which includes a predetermined amount of a compound containing aluminum and sulfur coated on the surface of a lithium titanium oxide, so that lithium ions do not occupy the 8a site during high-rate insertion, thereby having no kinetic effect, thereby minimizing the resistance increase rate accompanying the increase in the charge rate.
[0050] As a result, the negative electrode active material according to an embodiment of the present disclosure may be used in 12V or 48V secondary battery system applications.
[0051] In addition, the negative electrode active material according to an embodiment of the present disclosure may be used in automotive battery applications requiring high output, such as micro-hybrid batteries. BRIEF DESCRIPTION OF THE DRAWINGS
[0052] The accompanying drawings illustrate preferred embodiments of the present disclosure and, together with the following detailed description, are used to provide a further understanding of the technical aspects of the present disclosure; therefore, the present disclosure should not be construed as being limited to the accompanying drawings.
[0053] Figure 1 : is a graph showing the resistance increase rate of the secondary batteries manufactured in Examples 1 and 2 and Comparative Examples 1 and 2. DETAILED DESCRIPTION
[0054] Hereinafter, the present disclosure will be described in detail. Before the description, the terms or words used in the specification and the appended claims should not be interpreted as limited to the general meaning and dictionary meaning, but on the basis of the principle that the inventor is allowed to appropriately define the terms to provide the best interpretation, based on the meaning and concept corresponding to the technical aspects of the present disclosure. Therefore, the description disclosed herein and the illustrations shown in the accompanying drawings are only the most preferred embodiments, and are not intended to fully describe the technical aspects of the present disclosure, so it should be understood that other equivalents and variations may be made thereto when filing an application.
[0055] According to one aspect of the present disclosure, there is provided a negative electrode active material for a secondary battery, comprising:
[0056] A lithium-titanium composite, comprising:
[0057] Lithium titanium oxide (LTO) represented by the following Chemical Formula 1;
[0058] Zr doped into the lithium titanium oxide; and
[0059] a compound containing aluminum and sulfur coated on the surface of the lithium titanium oxide,
[0060] Wherein, based on 1M lithium titanium oxide, the aluminum and sulfur-containing compound is present in an amount of 0.4mM to 0.9mM:
[0061] [Chemical formula 1]
[0062] Li x Ti y O z
[0063] Where x, y and z satisfy 0.1≤x≤4, 1≤y≤5 and 2≤z≤12.
[0064] Generally, the negative electrode for high-output secondary batteries as an alternative to carbon-based negative electrodes is a negative electrode using lithium titanium oxide, and the lithium titanium oxide undergoes a two-phase reaction between a spinel structure and a rock salt structure by inserting and extracting lithium during charging and discharging. In this case, due to the two-phase reaction, even if the resistance is measured at the same SOC, the resistance value may vary depending on the direction (charging or discharging) of the set SOC, and the resistance value may also vary depending on the charge rate.
[0065] The above-mentioned inconsistent resistance value is caused by the structural characteristics of lithium titanium oxide, namely, lithium ions are inserted and deintercalated through the phase change between the spinel structure and the salt rock structure, and this problem may make the estimation algorithm very complicated because when a lithium secondary battery using lithium titanium oxide as the negative electrode active material is used in a battery pack, the estimation in the battery management system (BMS) is difficult.
[0066] However, as in the present disclosure, by using a negative electrode active material comprising a lithium-titanium based composite comprising lithium titanium oxide; Zr doped into the lithium titanium oxide; and a compound containing aluminum and sulfur coated on the surface of the lithium titanium oxide, the measured resistance value is low and constant regardless of the direction of setting the SOC and the charge rate, thereby overcoming the inherent resistance difference caused by the structural characteristics of the lithium titanium oxide.
[0067] In the case of conventional lithium titanium oxide, most lithium ions embedded during charge and discharge are located at the 8a site, and their positions do not change reversibly, resulting in an increase in resistance.
[0068] The negative electrode active material containing lithium titanium composite of the present disclosure comprises a compound containing aluminum and sulfur coated on the surface of lithium titanium oxide to form an interdiffusion layer on the surface, which increases the energy of Li entering the 8a site, so that lithium ions will not occupy the 8a tetrahedral site of the lithium titanium oxide during high rate insertion, and as a result, the position of the embedded lithium ions during charging and discharging can be reversibly changed. Lithium ions reversibly move between the two sites of 8a and 16c, but when the lithium migration to 8a is blocked, the inherent resistance difference caused by the structural characteristics of lithium titanium oxide can be overcome. Since the kinetic effect is not shown, the negative electrode active material containing lithium titanium composite of the present disclosure can be easily used in 12V or 48V secondary battery system applications.
[0069] The lithium secondary battery according to the present disclosure, which overcomes the inherent resistance difference caused by structural characteristics, can have minimal resistance change, for example, 5% or less or 3% or less, regardless of the direction in which the resistance is measured within the range between SOC 5 and 100 during charge and discharge.
[0070] In this case, the kinetic effect is the resistance difference between the pulse resistance measured after Li insertion (charging) into LTO at a low rate and the pulse resistance after insertion (charging) at a high rate.
[0071] The lithium titanium oxide may be, for example, Li 0.8 Ti 2.2 O4、Li 2.67 Ti 1.33 O4、Li 1.33 Ti 1.67 O4、Li 1.14 Ti 1.71 O4、Li4Ti5O 12 , LiTi2O4 and Li2TiO3, more specifically Li4Ti5O which has a small change in crystal structure during charge and discharge and has a good spinel structure 12 , Li 1.33 Ti 1.67 O4 or LiTi2O4. However, the lithium titanium oxide is not limited thereto.
[0072] According to one embodiment of the present disclosure, the lithium titanium oxide may be in the form of lithium titanium oxide primary particles, or in the form of secondary particles formed by agglomeration of the primary particles, or in the form of a mixture of the two.
[0073] In addition, according to one embodiment of the present disclosure, the lithium titanium oxide may include lithium titanium oxide secondary particles and a small amount of non-agglomerated free lithium titanium oxide primary particles, but the lithium titanium oxide may be substantially composed of secondary particles.
[0074] In order to obtain a lithium titanium oxide exhibiting high output characteristics, it is necessary to reduce the particle size and crystallite size of primary particles of the lithium titanium oxide.
[0075] When spaces are formed between primary particles of lithium titanium oxide and the primary particle size is reduced, the distance of Li ions in the particles is reduced and the reaction area of Li ions is increased, resulting in a significant improvement in output characteristics.
[0076] The lithium titanium oxide particles may have a grain size of 100 nm to 200 nm, specifically 110 nm to 180 nm, more specifically 140 nm to 160 nm.
[0077] When the grain size is less than 100 nm, a large number of grain boundaries are not conducive to the embedding of lithium ions and the charging characteristics of the battery may deteriorate, while when the grain size is greater than 200 nm, lithium ions have difficulty diffusing in the grains, resulting in increased resistance and reduced output.
[0078] The grain size of the lithium titanium oxide particles can be measured using the Rietveld refinement program Topaz. The grain size measurement method using the Topaz program may include a method commonly used in the technical field to which the present disclosure belongs.
[0079] In the lithium-titanium composite of the present disclosure, the lithium titanium oxide is doped with Zr. The doped Zr makes it easy for Li ions to diffuse.
[0080] Based on the weight of lithium titanium oxide, the amount of doped Zr may be 500 to 2000 ppm, or 700 to 1500 ppm, or 900 to 1100 ppm. When the amount of doped Zr satisfies the above range, the lattice constant may be slightly increased and the diffusion of Li ions may be increased, thereby providing a lithium secondary battery with improved output characteristics.
[0081] The aluminum and sulfur-containing compound is coated on the surface of the lithium titanium oxide to form an interdiffusion layer, which prevents Li from occupying the 8a site during fast charging (Li insertion).
[0082] The aluminum and sulfur containing compound may include Al2(SO4)3, Al2S3 or a combination thereof.
[0083] The amount of the compound containing aluminum and sulfur coated on the surface of the lithium titanium oxide is 0.4 mM to 0.9 mM, specifically 0.5 mM to 0.8 mM or 0.5 mM to 0.7 mM, based on 1 M of the lithium titanium oxide.
[0084] When the amount of the aluminum-and-sulfur-containing compound is lower than 0.4 mM, the interdiffusion layer is not fully formed and the kinetic effect cannot be reduced, while when the amount of the aluminum-and-sulfur-containing compound is higher than 0.9 mM, the thickness of the interdiffusion layer increases and the thickness of the side reaction layer (coating) on the surface increases, resulting in increased resistance and decreased capacity.
[0085] According to one embodiment of the present disclosure, the lithium titanium oxide may be further doped with Al, S (sulfur) or both. When the lithium titanium oxide is further doped with Al, S (sulfur) or both, the lattice constant of Li embedded in the 8a site from the surface is reduced, and Li cannot occupy the 8a site during high rate charging.
[0086] The lithium-titanium based composite may be primary particles, secondary particles formed by agglomeration of the primary particles, or a mixture of the primary particles and the secondary particles.
[0087] According to one embodiment of the present disclosure, an average particle diameter D50 of the primary particles may be equal to or less than 1 μm, and an average particle diameter D50 of the secondary particles may be 0.5 to 20 μm.
[0088] Here, D50 is an average particle diameter based on particle volume, and refers to a particle diameter corresponding to 50% of the total volume accumulated from small particles measured with a particle size distribution analyzer.
[0089] When the average particle size of the primary particles and the secondary particles satisfies the above range, the particle density can be increased and the electrode processing can be improved. When the average particle size is too small, a large amount of conductive material is required, which makes it impossible to form an electrode, and when the average particle size is too large, the output may be reduced.
[0090] The primary particles and / or the secondary particles may have a spherical or quasi-spherical shape. Here, the quasi-spherical shape has a 3-dimensional volume, includes an elliptical shape, and includes particles of all shapes, including amorphous particles having an indefinite shape.
[0091] In addition, in one embodiment of the present disclosure, the negative electrode active material layer has a pore structure having a plurality of pores. For example, the pore structure may be derived from at least one of the characteristics of the shapes of many lithium-titanium based composites described below.
[0092] The secondary particles of the lithium-titanium composite have a porous structure in which pores are formed on the surface and in the body of the secondary particles by pores formed between the agglomerated primary particles. In addition, the primary particles of the lithium-titanium composite may have a porous structure in which a plurality of primary pores are formed on the surface and in the body of the particles. The pores are connected to one or more adjacent pores, thereby serving as channels through which the electrolyte moves. Therefore, the pores formed in the particles and connected to each other serve as channels through which the electrolyte moves.
[0093] The lithium titanium oxide contained in the lithium titanium composite has a spinel structure and provides a 3-dimensional Li diffusion path, thereby being advantageous for fast charging and high output characteristics. In addition, the lithium titanium oxide maintains the original crystal structure during charging and discharging, thereby having high structural stability.
[0094] In addition, the lithium titanium oxide may have a capacity of 160 to 172 mAh / g, preferably 165 to 170 mAh / g, after lithiation.
[0095] In addition, the lithium titanium oxide may generate lithium carbonate as a by-product in an amount of 0.5 wt % or less or 0.2 wt % or less based on 100 wt % of the lithium titanium oxide.
[0096] According to one aspect of the present disclosure, there is provided a method for manufacturing a negative electrode active material for a secondary battery, the method comprising:
[0097] (a) mixing a lithium precursor, a titanium precursor and a Zr precursor to prepare a precursor mixture;
[0098] (b) heat-treating the precursor mixture at 700 to 1,100° C. to obtain lithium titanium oxide; and
[0099] (c) mixing the lithium titanium oxide obtained after the heat treatment with a compound containing aluminum and sulfur, and heat treating the mixture at 400 to 500° C.,
[0100] Wherein, the aluminum and sulfur containing compound is present in an amount of 0.4 mM to 0.9 mM based on 1 M lithium titanium oxide.
[0101] In detail, an example of a method of manufacturing a negative electrode active material for a secondary battery according to the present disclosure may be as follows.
[0102] First, (a) a lithium precursor, a titanium precursor, and a Zr precursor are mixed to prepare a precursor mixture.
[0103] The mixing of the precursor mixture in step (a) is a process for uniformly mixing the lithium precursor, the titanium precursor and the Zr precursor, and the mixing method is not limited to a specific type and may include any mixing method for uniformly mixing the precursor mixture in a dry state, and may include a wet mixing method and a dry mixing method.
[0104] The mixing may use a wet mixing method, for example, a wet mixing method using a spray drying process, where a lithium precursor, a titanium precursor, and a Zr precursor are added to a solvent and stirred to uniformly mix them to prepare a precursor composition. The precursor composition may be injected into a chamber having a spray dryer, and then the solvent is evaporated to produce a mixed precursor powder.
[0105] In detail, the precursor composition can be prepared by dissolving a lithium precursor and a titanium precursor in a solvent to prepare a composition and adding a Zr precursor while stirring the composition, and the volatile solvent used can include water such as deionized water or distilled water, an alcohol having a small number of carbon atoms such as methanol, ethanol or propanol, or acetone, and any solvent that can be easily evaporated by heat applied during spray drying can be used.
[0106] As described above, the prepared precursor composition may be injected into a chamber having a spray dryer, and the precursor composition may be sprayed by the spray dryer, and drying may be performed at the same time.
[0107] The spray dryer may include, for example, an ultrasonic spray dryer, an air nozzle spray dryer, an ultrasonic nozzle spray dryer, a filter expansion aerosol generator, an electrostatic spray dryer, or a combination thereof. Spray drying may preferably be performed at an internal chamber temperature of 20 to 300° C. When the temperature is higher than 300° C., the mixed precursor powder may agglomerate or grow particles, and thus appropriate temperature control is required.
[0108] The mixing may use a dry mixing method, and the dry mixing method may include mixing the lithium precursor, the titanium precursor, and the Zr precursor by a mechanical method, for example, the mixing method may use a ball mill, a high-speed rotary mill, a stirring mill, a jet mill, or a combination thereof.
[0109] The lithium precursor is not limited to a specific type and may include any source material capable of supplying lithium, such as a lithium salt including lithium ions and a salt, for example, Li2CO3, LiOH, LiF, Li2SO4, LiNO3, LiCl, or a combination thereof.
[0110] In addition, the titanium precursor is not limited to a specific type and may include any type of source material capable of supplying titanium, such as titanium oxide, and the titanium precursor may be in the form of a hydrate and a dry powder. In this case, when the titanium precursor is a hydrate, it may be desirable to use a wet mixing method to mix the titanium precursor with a lithium precursor, and when the titanium precursor is a dry powder, it may be desirable to use a dry mixing method. The titanium precursor may include, for example, TiO2, TiCl4, TiOCl2, TiOSO4, TiO(OH)2, or a combination thereof.
[0111] The Zr precursor may include Zr(OH)4, ZrO2, or a combination thereof.
[0112] Subsequently, (b) the precursor mixture is heat-treated at 700 to 1,100° C. to obtain lithium titanium oxide.
[0113] The step (b) may include heat treating the precursor mixture, and may be a sintering process for heat treating the mixed dry precursor powder by any method to produce lithium titanium oxide.
[0114] The heat treatment temperature or time may need to be appropriately controlled, and in terms of battery performance and safety, it may be necessary to prevent the lithium precursor, titanium precursor or Zr precursor from remaining unreacted and to avoid by-products such as lithium salts produced by side reactions, and it may be necessary to control the sintering conditions.
[0115] The heat treatment is performed at a temperature of 700 to 1,100°C, or about 750 to 1050°C, or 790 to 1000°C.
[0116] When the heat treatment temperature is lower than 700°C and sufficient heat is not supplied, unreacted lithium precursors or lithium salts such as lithium compounds due to side reactions may remain in the lithium titanium oxide, and when there are a large amount of residual impurities, side reactions or gas generation may occur and affect the storage performance or output characteristics of the battery, and when the heat treatment temperature is higher than 1,100°C, lithium titanium oxide degradation or particle growth may occur due to excessive energy supply and affect the output characteristics of the battery. Therefore, it may be necessary to appropriately control the heat treatment temperature.
[0117] It may also be necessary to control the heat treatment time, and in the present disclosure, the heat treatment may preferably be performed for about 2 to 12 hours or 5 to 10 hours. When the heat treatment time is met, structural stability can be ensured by sufficient grain growth and unnecessary energy waste or process cost consumption can be avoided.
[0118] Subsequently, (c) the lithium titanium oxide obtained after the heat treatment is mixed with a compound containing aluminum and sulfur, and the mixture is heat-treated at 400 to 500°C.
[0119] The mixing of the lithium titanium oxide obtained after the heat treatment and the compound containing aluminum and sulfur may use, but is not limited to, any method generally used for forming a coating layer, and as described above, wet mixing or dry mixing may be used.
[0120] For example, a compound containing aluminum and sulfur may be mixed with a dispersion medium, and the mixture may be added to the lithium titanium oxide obtained after heat treatment, and stirred and mixed to prepare a composition. Subsequently, the prepared composition may be dried and placed in a chamber having, for example, a spray dryer, followed by solvent evaporation to prepare a mixed precursor powder. In this case, the spray dryer is as described above.
[0121] Subsequently, the dried resultant is heat treated at 400 to 500° C., or may be heat treated at 400 to 480° C. or 400 to 450° C. When the heat treatment temperature is outside the above conditions, coating cannot be achieved, or doping is performed without forming an interdiffusion layer.
[0122] In addition, as described above, the aluminum and sulfur-containing compound coated on the surface of the lithium titanium oxide is present in an amount of 0.4 to 0.9 mM, specifically, 0.5 to 0.8 mM or 0.5 to 0.7 mM based on 1 M lithium titanium oxide.
[0123] In one embodiment of the present disclosure, the loading amount of the negative electrode active material on the negative electrode can be 0.2 mAh / cm 2 Up to 2mAh / cm 2 .
[0124] According to a specific embodiment of the present disclosure, the negative electrode active material layer may further include a binder resin and a conductive material. Here, the negative electrode active material layer may include a negative electrode active material: conductive material: binder resin in a weight ratio of 80 to 90:7 to 13:3 to 9.
[0125] In addition, in addition to lithium titanium oxide, the negative electrode active material layer may also contain particles of at least one active material selected from the group consisting of carbonaceous materials commonly used as negative electrode active materials, such as natural graphite, artificial graphite; metals (Me), including Si, Sn, Li, Zn, Mg, Cd, Ce, Ni or Fe; alloys of metals (Me); oxides (MeOx) of metals (Me); and composites of metals (Me) and carbon as negative electrode active materials.
[0126] Non-limiting examples of the binder resin may include at least one selected from the group consisting of polyvinylidene fluoride-co-hexafluoropropylene, polytetrafluoroethylene (PTFE), polyvinylidene fluoride (PVDF), carboxymethyl cellulose (CMC), polyvinyl alcohol (PVA), polyvinyl butyral (PVB), poly-N-vinyl pyrrolidone (PVP), styrene butadiene rubber (SBR), polyamide-imide and polyimide, but are not limited thereto.
[0127] The conductive material is not limited to a specific type and may include any electron conductive material that does not cause chemical changes, such as natural graphite, artificial graphite, carbon black, acetylene black, Ketjen black, Super-P black, carbon fiber, metal powder or metal fiber of copper, nickel, aluminum, silver.
[0128] In a specific embodiment of the present disclosure, the negative electrode can be manufactured by the following method. First, the negative electrode active material, the binder resin and the conductive material are dispersed in a suitable solvent to prepare a negative electrode slurry, the solvent is such as an organic solvent or water, the organic solvent is such as ethanol (EtOH), acetone, isopropanol, N-methylpyrrolidone (NMP) and propylene glycol (PG), the negative electrode slurry is pressed into an electrode shape, or the slurry is coated on a metal foil to form an electrode shape, or the negative electrode composition is rolled into a sheet state and attached to a metal foil to form an electrode, and the electrode-shaped formation is dried at a temperature of 100°C to 350°C to form a negative electrode. Describing the example of forming the negative electrode in more detail, the negative electrode slurry can be formed by pressing using a roll forming machine. The roll forming machine is designed to improve the electrode density and control the electrode thickness by pressing, and the roll forming machine includes an upper roller and a lower roller, a controller for controlling the roller thickness and the heating temperature, and a winding unit for winding and unwinding the electrode. The electrode wound into a roll form is pressed while passing through a roller press and is wound into a roll form again to complete the electrode. In this case, the pressure applied by pressing is preferably 5 to 20 tons / cm 2 And the temperature of the roller is preferably 0 to 150°C. Then, the slurry subjected to the rolling process is dried. The drying process is carried out at a temperature of 100°C to 350°C, preferably 150°C to 300°C. In this case, when the drying temperature is lower than 100°C, the solvent is difficult to evaporate, and when the drying is carried out at a high temperature higher than 350°C, oxidation of the conductive material may occur. Therefore, preferably, the drying temperature is equal to or higher than 100°C and not more than 350°C. In addition, the drying process is preferably carried out at the temperature as described above for about 10 minutes to 6 hours. The drying process can keep the powder particles together while drying the shaped negative electrode composition (solvent evaporation), thereby improving the strength of the negative electrode.
[0129] The lithium secondary battery of the present disclosure includes the above-mentioned negative electrode and positive electrode, a separator interposed between the positive electrode and the negative electrode, and an electrolyte.
[0130] The positive electrode can be manufactured by bonding the positive electrode active material to the positive electrode current collector by conventional methods known in the art to which the present disclosure belongs. Non-limiting examples of the positive electrode active material may include positive electrode active materials commonly used in positive electrodes of electrochemical devices, and are preferably lithium manganese oxide, lithium cobalt oxide, lithium nickel oxide, lithium iron oxide or lithium composite oxide thereof. Non-limiting examples of the positive electrode current collector may include foil made of aluminum, nickel or a combination thereof.
[0131] The separator may include a single porous substrate having a plurality of pores, or a porous substrate in combination with a porous coating layer including inorganic particles and a binder polymer coated on at least one surface of the porous substrate.
[0132] The porous substrate may be a porous polymer substrate, specifically, a porous polymer film substrate or a porous polymer nonwoven fabric substrate.
[0133] The porous polymer film substrate may be a porous polymer film made of polyolefin such as polyethylene and polypropylene, and the polyolefin porous polymer film substrate exhibits a closed-cell function at a temperature of, for example, 80 to 130°C.
[0134] In addition, the porous polymer film substrate can be formed into a film shape using various types of polymers such as polyolefins and polyesters. In addition, the porous polymer film substrate can be formed by stacking more than two film layers, and each film layer can be formed by polymers such as polyolefins and polyesters as described above used alone or in combination.
[0135] In addition, in addition to the above-mentioned polyolefins, the porous polymer film substrate and the porous nonwoven fabric substrate may be formed of polyethylene terephthalate, polybutylene terephthalate, polyester, polyacetal, polyamide, polycarbonate, polyimide, polyetheretherketone, polyethersulfone, polyphenylene ether, polyphenylene sulfide and polyethylene naphthalate, used alone or in combination. The thickness of the porous substrate is not particularly limited, but is preferably 1 to 100 μm, more preferably 5 to 50 μm, and the pore size and porosity of the porous substrate are not particularly limited, but the pore size is preferably 0.01 to 50 μm and the porosity is preferably 10% to 95%.
[0136] In the separator according to one aspect of the present disclosure, the binder polymer used to form the porous coating layer may include a polymer commonly used in the technical field to which the present disclosure belongs for forming the porous coating layer. In particular, the glass transition temperature T g The polymer is -200°C to 200°C to improve the mechanical properties of the finally formed porous coating layer, such as flexibility and elasticity. The binder polymer faithfully functions as a binder that connects and stably fixes the inorganic particles, helping to prevent the mechanical properties of the separator having the porous coating layer from deteriorating.
[0137] In addition, the binder polymer does not need to be able to transport ions, but the use of polymers that can transport ions can further improve the performance of the electrochemical device. Therefore, the binder polymer may include those binder polymers with as high a dielectric constant as possible. The degree of dissociation of the salt in the electrolyte depends on the dielectric constant of the electrolyte solvent, and as the dielectric constant of the binder polymer increases, the degree of dissociation of the salt in the electrolyte may increase. The dielectric constant of the binder polymer can be in the range of 1.0 to 100 (measurement frequency = 1kHz), and specifically 10 or more.
[0138] In addition to the above functions, the binder polymer can exhibit a high degree of swelling in the electrolyte by gelling when impregnated with the liquid electrolyte. Therefore, the solubility parameter (i.e., Hildebrand solubility parameter) of the binder polymer is between 15 and 45 MPa. 1 / 2 Between or between 15 and 25 MPa 1 / 2 Between 30 and 45 MPa 1 / 2 Therefore, hydrophilic polymers with polar groups can be used instead of hydrophobic polymers such as polyolefins. When the solubility parameter is lower than 15 MPa 1 / 2 and above 45MPa 1 / 2 When the binder polymer is used, it is possible that the binder polymer does not swell in conventional liquid electrolytes for batteries.
[0139] Non-limiting examples of the binder polymer may include polyvinylidene fluoride-co-hexafluoropropylene, polyvinylidene fluoride-co-trichloroethylene, polymethyl methacrylate, polybutyl acrylate, polyacrylonitrile, polyvinyl pyrrolidone, polyvinyl acetate, polyethylene-co-vinyl acetate, polyethylene oxide, polyarylate, cellulose acetate, cellulose acetate butyrate, cellulose acetate propionate, cyanoethyl pullulan, cyanoethyl polyvinyl alcohol, cyanoethyl cellulose, cyanoethyl sucrose, pullulan and carboxymethyl cellulose, but are not limited thereto.
[0140] The weight ratio of the inorganic particles to the binder polymer is, for example, preferably in the range of 50:50 to 99:1, more preferably in the range of 70:30 to 95:5. When the ratio of the inorganic particles to the binder polymer satisfies the above range, the decrease in the pore size and porosity of the formed coating layer due to the high content of the binder polymer and the decrease in the peeling resistance of the formed coating layer due to the low content of the binder polymer can be prevented.
[0141] In the porous coating layer, inorganic particles are stacked in a contacting manner such that the inorganic particles are held together by the binder polymer to form interstitial volumes therebetween, and the interstitial volumes are empty spaces that become pores.
[0142] That is, the binder polymer can bind the inorganic particles to keep them together, for example, the binder polymer adheres and fixes the inorganic particles. In addition, the interstitial volume between the inorganic particles is the empty space that becomes the pore of the porous coating, and they are the spaces defined by the inorganic particles that are substantially in surface contact in the structure formed by the close packing or dense packing of the inorganic particles.
[0143] The inorganic particles are selected from the group consisting of inorganic particles having a dielectric constant of about 5 or more, inorganic particles capable of transporting lithium ions, and combinations thereof.
[0144] According to one embodiment of the present disclosure, the electrolyte comprises a + B - Here, A + Contains alkali metal cations such as Li + 、Na + , K + or a combination thereof, preferably Li + Ion. B - Contains anions such as F - , Cl - Br - ,I - 、NO3 - 、BF4 - PF6 - 、N(CN)2 - 、SCN - 、ClO4 - 、AsF6 - CF3SO3 - 、(CF3SO2)2 - 、C(CF2SO2)3 - 、(CF3)3PF3 - 、(CF3)4PF2 - 、(CF3)5PF - 、(CF3)6P - , (CF3CF2SO2 - )2N, (CF3SO2)2N - CF3SO3 - CF3CF2(CF3)2CO - 、(CF3SO2)2CH - 、(CF3SO2)3C - CF3(CF2)7SO3 - CF3CO2 - 、CH3CO2 - or a combination thereof. Preferably, the A + B - The salt of the structure is a lithium salt.
[0145] The A + B -The salt of the structure dissolves and dissociates in an organic solvent. Non-limiting examples of the organic solvent may include propylene carbonate (PC), ethylene carbonate (EC), diethyl carbonate (DEC), dimethyl carbonate (DMC), dipropyl carbonate (DPC), dimethyl sulfoxide, acetonitrile, dimethoxyethane, diethoxyethane, tetrahydrofuran, N-methyl-2-pyrrolidone (NMP), ethyl methyl carbonate (EMC), gamma-butyrolactone or a combination thereof.
[0146] The electrolyte injection can be performed in any suitable step of the battery manufacturing process according to the manufacturing process and the required performance of the final product. That is, the electrolyte injection can be applied before the battery assembly or in the last step of the battery assembly.
[0147] According to an aspect of the present disclosure, there are provided a battery module including a lithium secondary battery as a unit battery, and a battery pack including the battery module.
[0148] As described above, the lithium secondary battery of the present disclosure uses a lithium-titanium composite as a negative electrode active material to achieve improved output characteristics without actually causing a decrease in high temperature characteristics and battery capacity, and when the lithium secondary battery is used as a replacement or supplement for an automotive lead-acid battery, a battery pack with improved efficiency can be provided.
[0149] The battery pack may include lithium secondary batteries connected in series, or may include lithium secondary battery modules connected in series, each lithium secondary battery module including lithium secondary batteries connected in parallel.
[0150] The battery pack can be used as a power source for devices that require high temperature stability, long cycle characteristics, and high rate characteristics. For example, the device may include, but is not limited to, an electric tool that is driven and operated by power derived from an electric motor; a vehicle, including an electric vehicle (EV), a micro-hybrid electric vehicle (u-HEV), a hybrid electric vehicle (HEV), and a plug-in hybrid electric vehicle (PHEV); an electric two-wheeler, including an electric bicycle and an electric scooter; an electric golf cart; and an energy storage system.
[0151] Hereinafter, the present disclosure will be described in detail by means of embodiments. However, the embodiments of the present disclosure may be modified in many other forms, and the scope of the present disclosure should not be construed as being limited to the following embodiments. The embodiments of the present disclosure are provided to fully explain the present disclosure to those of ordinary skill in the art to which the present disclosure belongs.
[0152] Example 1
[0153] 42.8 parts by weight of Li2CO3 as a lithium precursor and 57.2 parts by weight of TiO2 as a titanium precursor were mixed with 50 parts by weight of water and placed in a ball mill, where the mixture was ground and stirred for 60 minutes to ensure uniform mixing, and then Zr(OH)4 as a Zr precursor was added at a concentration of 1,000 ppm based on the weight of the lithium titanium oxide to prepare a precursor composition. The prepared precursor composition was spray-dried to obtain a spherical precursor, and the spherical precursor was heat-treated in a furnace at a temperature of 790° C. for 10 hours to obtain lithium titanium oxide (Li4Ti5O 12 The obtained lithium titanium oxide (Li4Ti5O 12 ) and water to prepare 1M lithium titanium oxide (Li4Ti5O 12 ) aqueous solution. And 0.7mM of Al2(SO4)3 was added thereto, followed by stirring with a stirrer and spray drying to obtain a mixture. The obtained mixture was heat-treated in a furnace at a temperature of 450°C for 5 hours to prepare a lithium-titanium composite. In this case, the obtained lithium-titanium composite was a secondary particle having an average particle size D50 of 16μm. The prepared lithium-titanium composite comprises an aluminum- and sulfur-containing compound coated on the surface of lithium titanium oxide, and the aluminum- and sulfur-containing compound is present in an amount of 0.7mM based on 1M lithium titanium oxide. The doping amount of Zr is 1,000ppm based on the weight of the lithium titanium oxide.
[0154] 92 wt% of a synthetic lithium-titanium composite, 4 wt% of carbon black as a conductive material, and 4 wt% of polyvinylidene fluoride (PVdF) as a binder were added to N-methyl-2-pyrrolidone (NMP) as a solvent to prepare a negative electrode mixture slurry. The prepared negative electrode mixture slurry was coated on one surface of an aluminum (Al) film having a thickness of about 20 μm as a negative electrode current collector, and then dried and rolled to manufacture a negative electrode having an active material layer with a porosity of about 33%.
[0155] <Manufacturing of positive electrode>
[0156] 96 wt% of LiMn2O4 and Li(Ni 0.33 Co 0.33 Mn 0.33 A mixture of 20 wt % of MgO2, 2 wt % of carbon black as a conductive material, and 2 wt % of polyvinylidene fluoride (PVdF) as a binder were added to N-methyl-2-pyrrolidone (NMP) as a solvent to prepare a positive electrode mixture slurry. The positive electrode mixture slurry was coated on one surface of an aluminum (Al) thin film having a thickness of about 20 μm as a positive electrode current collector, and then dried and rolled to manufacture a positive electrode.
[0157] <Manufacturing of lithium secondary batteries>
[0158] A lithium secondary battery was manufactured by a conventional method using the above-mentioned positive and negative electrodes together with a separator of a polypropylene / polyethylene / polypropylene (PP / PE / PP) three-layer structure, and then injected with an electrolyte containing 1M LiPF6 dissolved in a mixed solvent of ethylene carbonate (EC) and diethyl carbonate (DEC) in a volume ratio of 30:70.
[0159] <Manufacturing of Half-Cell>
[0160] The half-cell was fabricated as follows.
[0161] 0.4 g of a binder solution (containing 5 wt % polyvinylidene fluoride (PVdF) dissolved in N-methylpyrrolidone (NMP)) was added to 0.98 g of the lithium titanium based composite prepared above and mechanically stirred to prepare a slurry (weight ratio of LTO-A:PVdF was 98:2).
[0162] The slurry was coated on an aluminum foil to a thickness of 90 μm, and dried at 120° C. in a vacuum to manufacture a negative electrode.
[0163] Subsequently, the negative electrode was wound into a circular shape with a diameter of 12 mm, and a 2032-type coin half-cell was manufactured using lithium metal (foil) as a counter electrode. In this case, the electrolyte used was a solution obtained by dissolving 1.3 M LiPF6 in a mixed solvent of ethylene carbonate, diethyl carbonate, and ethyl methyl carbonate in a volume ratio of 3:5:2.
[0164] Example 2
[0165] The obtained lithium titanium oxide (Li4Ti5O 12 ) and water to prepare 1M lithium titanium oxide (Li4Ti5O 12 ) aqueous solution, and added 0.5 mM Al2(SO4)3 thereto, followed by stirring with a stirrer and spray drying to obtain a mixture, and the mixture was heat-treated in a furnace at a temperature of 400°C for 5 hours. Except for the above, a negative electrode and a secondary battery were prepared by the same method as in Example 1.
[0166] The prepared lithium titanium based composite includes a compound containing aluminum and sulfur coated on the surface of lithium titanium oxide, and the compound containing aluminum and sulfur is present in an amount of 0.5 mM based on 1 M of lithium titanium oxide.
[0167] Comparative Example 1
[0168] The obtained lithium titanium oxide (Li4Ti5O 12) is added to the Al2(SO4)3 aqueous solution and the spray is dried, i.e., the lithium titanium oxide (Li4Ti5O 12 ) is coated with Al2(SO4)3. Except for the above, a negative electrode and a secondary battery are prepared by the same method as in Example 1.
[0169] Comparative Example 2
[0170] The obtained lithium titanium oxide (Li4Ti5O 12 ) and water to prepare 1M lithium titanium oxide (Li4Ti5O 12 ) aqueous solution, and 0.3mM of Al2(SO4)3 was added thereto, followed by stirring with a stirrer and spray drying to obtain a mixture, and the mixture was heat-treated in a furnace at a temperature of 400°C for 5 hours. Except for the above, a negative electrode and a secondary battery were prepared by the same method as in Example 1. The prepared lithium-titanium composite comprises a compound containing aluminum and sulfur coated on the surface of lithium titanium oxide, and the compound containing aluminum and sulfur is present in an amount of 0.3mM based on 1M lithium titanium oxide.
[0171] Comparative Example 3
[0172] The obtained lithium titanium oxide (Li4Ti5O 12 ) and water to prepare 1M lithium titanium oxide (Li4Ti5O 12 ) aqueous solution, and added 1.0 mM Al2(SO4)3 thereto, followed by stirring with a stirrer and spray drying to obtain a mixture, and the mixture was heat-treated in a furnace at a temperature of 450°C for 5 hours. Except for the above, a negative electrode and a secondary battery were prepared by the same method as in Example 1.
[0173] The prepared lithium titanium based composite includes a compound containing aluminum and sulfur coated on the surface of lithium titanium oxide, and the compound containing aluminum and sulfur is present in an amount of 1.0 mM based on 1 M of lithium titanium oxide.
[0174] Comparative Example 4
[0175] The obtained lithium titanium oxide (Li4Ti5O 12 ) and water to prepare 1M lithium titanium oxide (Li4Ti5O 12 ) aqueous solution, and 0.2 mM trimethylaluminum (TMA) was added thereto, followed by stirring with a stirrer and spray drying to obtain a mixture, and the mixture was heat-treated in a furnace at a temperature of 450° C. for 5 hours. Except for the above, a negative electrode and a secondary battery were prepared by the same method as in Example 1.
[0176] Characteristic measurement
[0177] Evaluation of memory effect (kinetic effect)
[0178] (1) Evaluation of Examples 1 to 2 and Comparative Examples 1 to 2
[0179] The secondary batteries manufactured in Examples 1 to 2 and Comparative Examples 1 to 2 were charged to SOC 20% at 1C, 25°C, then charged to a target SOC at 1C, and subsequently charged at 35C, and the charging resistance 1 was measured.
[0180] In addition, the secondary batteries manufactured in Examples 1 to 2 and Comparative Examples 1 to 2 were charged to SOC 20% at 1C, 25°C, then charged to a target SOC at 10C, and subsequently charged at 35C, and the charging resistance 2 was measured.
[0181] The resistance increase rate (%) was calculated by the following formula using the measured charging resistance 1 and charging resistance 2.
[0182] Resistance increase rate (%) = (charging resistance 2 – charging resistance 1) / (charging resistance 1) × 100
[0183] The target SOC was changed to 30%, 50%, 60%, 70%, 80%, 90%, and the resistance increase rate of the secondary batteries manufactured in Examples 1 to 2 and Comparative Examples 1 to 2 was measured, and the results are shown in Tables 1 and Figure 1 Shown in.
[0184] (2) Evaluation of Comparative Examples 3 and 4
[0185] In the secondary battery of Comparative Example 3, a larger amount of the compound containing aluminum and sulfur than the threshold value was coated on the surface of the lithium titanium oxide, and the capacity was too low to evaluate the resistance.
[0186] The resistance increase rate (%) of the secondary battery of Comparative Example 4 was calculated by the above formula using only the charging resistance 1 and the charging resistance 2 at SOC 90%, and the results are shown in Table 1. No measurement was performed at other SOCs.
[0187]
Table 1
[0188]
[0189] Refer to Table 1 and Figure 1, it can be seen that, when compared with Comparative Examples 1, 2 and 4, the secondary batteries of Examples 1 and 2 have a very low resistance increase rate even if the SOC (%) increases. It can be understood that the negative electrode active material used in the secondary batteries of Examples 1 and 2 includes a lithium-titanium composite, which includes a predetermined amount of aluminum- and sulfur-containing compounds coated on the surface of lithium titanium oxide, so that lithium ions do not occupy the 8a site during high-rate insertion, and therefore there is no kinetic effect, thereby minimizing the resistance increase rate accompanying the increase in the charge rate.
Claims
1. A negative electrode active material for a lithium secondary battery, comprising: A lithium-titanium composite, comprising: Lithium titanium oxide represented by the following Chemical Formula 1; Zr doped into the lithium titanium oxide; and a compound containing aluminum and sulfur coated on the surface of the lithium titanium oxide, in, The aluminum and sulfur containing compound is present in an amount of 0.4 mM to 0.9 mM based on 1 M lithium titanium oxide: [Chemical formula 1] Li x You y ON z where x, y and z satisfy 0.1≤x≤4, 1≤y≤5 and 2≤z≤12, wherein the amount of the doped Zr is 500 to 2000 ppm based on the weight of the lithium titanium oxide, The negative electrode active material can be used in 12V or 48V secondary battery system applications. 2 . The negative electrode active material for a lithium secondary battery according to claim 1 , wherein the compound containing aluminum and sulfur comprises Al 2 (SO 4 ) 3 , Al 2 S 3 or a combination thereof. 3 . The negative electrode active material for a lithium secondary battery according to claim 1 , wherein the lithium-titanium based composite is a primary particle, a secondary particle formed by agglomeration of the primary particles, or a mixture of the primary particles and the secondary particles. 4 . The negative electrode active material for a lithium secondary battery according to claim 3 , wherein an average particle diameter D50 of the primary particles is equal to or less than 1 μm. 5 . The negative electrode active material for a lithium secondary battery according to claim 3 , wherein an average particle diameter D50 of the secondary particles is 0.5 to 20 μm. 6 . The negative electrode active material for a lithium secondary battery according to claim 1 , wherein the compound containing aluminum and sulfur is present in an amount of 0.5 mM to 0.8 mM based on 1 M lithium titanium oxide. 7 . The negative electrode active material for a lithium secondary battery according to claim 1 , wherein the lithium titanium oxide is further doped with Al, S, or both.
8. A method for producing a negative electrode active material for a lithium secondary battery according to any one of claims 1 to 7, comprising: (a) mixing a lithium precursor, a titanium precursor and a Zr precursor to prepare a precursor mixture; (b) heat-treating the precursor mixture at 700 to 1,100° C. to obtain lithium titanium oxide; and (c) mixing the lithium titanium oxide obtained after the heat treatment with a compound containing aluminum and sulfur, and heat-treating the mixture at 400 to 500° C., Wherein, the aluminum and sulfur containing compound is present in an amount of 0.4 mM to 0.9 mM based on 1 M lithium titanium oxide. 9 . The method for manufacturing a negative electrode active material for a lithium secondary battery according to claim 8 , wherein the lithium precursor comprises Li 2 CO 3 , LiOH, LiF, Li 2 SO 4 , LiNO 3 , LiCl or a combination thereof.
10. The method for manufacturing a negative electrode active material for a lithium secondary battery according to claim 8, wherein the titanium precursor comprises TiO2, TiCl4, TiOCl2, TiOSO4, TiO(OH)2 or a combination thereof.
11. The method for manufacturing a negative electrode active material for a lithium secondary battery according to claim 8, wherein the Zr precursor comprises Zr(OH)4, ZrO2 or a combination thereof. 12 . The method for manufacturing a negative electrode active material for a lithium secondary battery according to claim 8 , wherein the compound containing aluminum and sulfur comprises Al 2 (SO 4 ) 3 , Al 2 S 3 or a combination thereof.
13. The method for manufacturing a negative electrode active material for a lithium secondary battery according to claim 8, wherein the temperature of the heat treatment performed after mixing the lithium titanium oxide with the aluminum and sulfur-containing compound is 400 to 480°C, and the aluminum and sulfur-containing compound is present in an amount of 0.5 to 0.8 mM based on 1 M of the lithium titanium oxide. 14 . The method of manufacturing a negative electrode active material for a lithium secondary battery according to claim 8 , wherein the heat treatment temperature is 450° C., and the compound containing aluminum and sulfur is present in an amount of 0.7 mM based on 1 M lithium titanium oxide.
15. A lithium secondary battery comprising: a positive electrode comprising a positive electrode active material, a negative electrode comprising a negative electrode active material, a separator between the positive electrode and the negative electrode, and Electrolyte, in, The negative electrode active material is defined in any one of claims 1 to 7.
Citation Information
Patent Citations
Method for manufacturing a flavor inhaler and a combustion heat source
KR1020190021445A
Doped lithium titanium spinel compound and electrode comprising same
CN104081565A
Lithium titanate powder for electrode of power storage device, active substance material, and power storage device using same.
CN106415899A
Anode active material comprising titanium-based composite, manufacturing method therefor, and lithium secondary battery comprising same
CN107851788A